Effects of past and present microclimates on northern and southern plant species in a managed forest landscape - Christiansen, Ditte Marie; Strydom, Tanya; Greiser, Caroline; McClory, Ryan; Ehrlén, Johan; Hylander, Kristoffer (Journal of vegetation science, 2023)
Questions Near‐ground temperatures can vary substantially over relatively short distances, enabling species with different temperature preferences and geographical distributions to co‐exist within a small area. In a forest landscape, the near‐ground temperatures may change due to management activities that alter forest density. As a result of such management activities, current species distributions and performances might not only be affected by current microclimates, but also by past conditions due to time‐lagged responses. Location Sweden. Methods We examined the effects of past and current microclimates on the distributions and performances of two northern, cold‐favoured, and two southern, warm‐favoured, plant species in 53 managed forest sites. Each pair was represented by one vascular plant and one bryophyte species. We used temperature logger data and predictions from microclimate models based on changes in basal area to relate patterns of occurrence, abundance, and reproduction to current and past microclimate. Results The two northern species were generally favoured by microclimates that were currently cold, characterised by later snowmelt and low accumulated heat over the growing season. In contrast, the two southern species were generally favoured by currently warm microclimates, characterised by high accumulated heat over the growing season. Species generally had higher abundance in sites with a preferred microclimate both in the past and present, and lower abundance than expected from current conditions, if the past microclimate had changed from warm to cold or vice versa, indicating time‐lags in abundance patterns of the species. Conclusions Our results show a potential importance of past and present microclimate heterogeneity for the co‐existence of species with different temperature preferences in the same landscape and highlight the possibility to manage microclimates to mitigate climate change impacts on forest biodiversity. We show an importance of past and present microclimate heterogeneity for the regional co‐existence of understory plant species with different temperature preferences growing in managed forest landscapes. Northern (a, c) and southern (b, d) species were generally favoured by current cold and warm microclimates, respectively. Past microclimate showed effects on current abundance patterns, suggesting time‐lags in responses of species to altered microclimate are important.